Protection of Personal Information in the Medical Sphere of Social Relations - Yankovyi, Mykola O.; Foros, Hanna V.; Zaiets, Hanna V.; Pluzhnik, Olena I. (Cuestiones Políticas, 2020)
The purpose of the work was to identify the main legal parameters of modern information. As material sources of research at work, not only the Ukrainian regulations in the field of medical relations information are used, but also relevant innovations in the legal regulation of medical information relations, which are produced in the countries of the European Union. It is established that in the normative legal acts of Ukraine, unlike in European legislation, there is no division of information about an individual into general data and vulnerable personal data. The laws of Ukraine do not contain the notion of "public figure", whose limits of criticism, according to the European Court of Human Rights, are broader for an ordinary person. Among the main conclusions, it stands out that, in order to guarantee the freedoms and rights of citizens, it is necessary in the regulations to classify groups, lists of personal data and access to them based on the secret classification to avoid ambiguities. The materials in the article have practical value for graduates of higher education institutions of police and medical specialties, among others.